The role and perception of accountants on environmental management accounting in an emerging market: Study on South Africa’s companies. - Thomas Nyahuna; Mishelle Doorasamy (Graduate School Bogor Agricultural University (SPs IPB), 2022)
This research explores the role and views of accountants in environmental management accounting (EMA) and environmental performance. The study relied on a survey of 86 chief finance officers, accountants and finance managers from the top 40 listed South African companies. The chief finance officers, accountants and finance managers confess that they lack understanding on in what way environmental issues can be incorporated into EMA. In addition, the professionals disclose that EMA has not had an ample consideration by their companies. This suggests that a limited involvement by the accountants in EMA in South Africa exists. Hence, the sampled chief finance officers, accountants and finance managers indicated that they are not sure of their potential responsibility. This shows that South African accountants are noticeably absent from participating in EMA. This has been ascribed to EMA being a new branch of accounting, their little aptitude in environmental issues and also the voluntary nature bestowed on EMA practices. Therefore, this paper will increase literature on the views of accountants on EMA from a developing country’s perspective.